FREQUENCY OF ALBUMINURIA IN DIABETIC PATIENTS PRESENTING WITH MACROVASCULAR COMPLICATIONS - Sohail, Muhammad; Fatima, Fozia; Fatima, Sadia; Khan, Shahbaz Ali; Anwar, Syed Abbas; Alam, Muhammad Adeel; Abbasi, Munir Ahmad (Journal of Ayub Medical College Abbottabad, 2014)
Background: Diabetes mellitus is major cause of morbidity and premature mortality from its long term complications such as cardiovascular disease, blindness, renal failure, amputation and stroke. The study was conducted to determine the frequency of albuminuria in diabetic patients presenting with macro-vascular complications like myocardial infarction (MI) and stroke. Methods: This descriptive study was conducted at Ayub Medical College, Abbottabad from December 2010 to May 2011. Total 88 diabetic patients admitted with macro-vascular disease were included in this study. The patients were subjected to two urine specimen’s examination, one for routine examination for infection and dipstick analysis for albuminuria. Second was tested for albumin was tested in the urine. Results: Out of 88 patients with a mean 47.12±7.58 years, 39 (44.32%) were female while 49 (55.68%) were male. Overall albuminuria was detected in the urine of 81 out of total 88 patients (92%) when tested by heating method whereas it was detected in 41 (46.6%) cases by the dipstick method. Conclusion: Frequency of albuminuria is much higher in diabetic population with macro-vascular complications; hence albumin in the urine of diabetic patient can be regarded as an indicator for impending macro-vascular complications of diabetes. Keywords: Diabetes mellitus, macro-vascular disease, albuminuria, complications, CVA